Preparation of polypropylene thermoplastic container via thermoforming process - Nik Ruqiyah, Nik Hassan; Farah Amira, Mohd Ghazali; Abdul Aziz, Jaafar; Noor Mazni, Ismail (IOP Publishing, 2016)
In this study, plastic containers made of polypropylene (PP) sheets were fabricated via vacuum thermoforming. Thermoforming is a process used in fabricating plastic parts by changing flat thermoplastic sheet to three dimensional shapes. In preparing these thermoplastic containers, the design and fabrication of mould were first done by using Catia V5 software and CNC milling machine, respectively. The thermoforming process was then performed at various temperatures ranging from 160°C until 200°C on the PP sheet to form the container. From the experiment, it can be suggested that the outcomes of final thermoplastic containers are significantly depends on temperature control during thermoforming process and also the vent holes design of the mould.